Сost-effectiveness of preventing cardiovascular death and achieving the target indicator "Reduction of the cardiovascular mortality of the population" of the State Program "Health Development" when using valsartan+sacubitril, dapagliflozin and empagliflozin in patients with heart failure with reduced ejection fraction - M. V. Zhuravleva; S. N. Tereshchenko; I. V. Zhirov; S. V. Nedogoda; Yu. V. Gagarina; E. A. Shabalina (Российский кардиологический журнал)
Aim. To evaluate the cost-effectiveness of achieving the target indicator "Reduction of the cardiovascular mortality of the population" of the State Program "Health Development" when using drugs valsartan+sacubitril, dapagliflozin and empagliflozin in patients with New York Heart Association (NYHA) class II-IV heart failure with reduced ejection fraction ≤40% s in 2023-2024.Material and methods. The target population was Russian patients who received preferential medicines in the last two years after an acute cardiovascular disease. The population size was determined on the basis of Russian literary and statistical sources. To predict the cardiovascular death, a parametric modeling method was used based on published data from clinical trials. The amount of drug costs required to prevent one cardiovascular death, as well as to achieve a one target for reducing cardiovascular mortality, was calculated using each of the comparator drugs in the whole country and separately in each region.Results. The cost of drugs for the 1st year of therapy to prevent one cardiovascular death in the case of valsartan+sacubitril was RUB 3,99 million, dapagliflozin — RUB 2,63 million, empagliflozin — RUB 4,43 million. There were following costs required to achieve one target indicator for reducing cardiovascular mortality of the State Program "Health Development" for valsartan+sacubitril, dapagliflozin and empagliflozin:in 2023 — RUB 2197,9 million, RUB 1451,5 million and RUB 2435,9 million, respectively;in 2024 — RUB 627,4 million, RUB 407,7 million and RUB 706,9 million, respectively.Conclusion. Among the agents considered, dapagliflozin seems to be the most cost effective for preventing one cardiovascular death and achieving one of the target "Reduction of the cardiovascular mortality" of the State Program "Health Development" in 2023-2024.